2020
DOI: 10.1186/s12906-020-02955-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acupuncture on occipital neuralgia: a systematic review and meta-analysis

Abstract: Background: Occipital neuralgia is one of the main causes of occipital pain. This systematic review aims to assess the level of evidence in randomized controlled trials (RCTs) on the effects of acupuncture on occipital neuralgia. Methods: We searched 11 databases and a journal archive from their inception up to December 2019 for relevant RCTs. We did not place any specific restrictions on patients diagnosed with occipital neuralgia, such as age or gender. We included studies that used an acupuncture interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 25 publications
(19 reference statements)
0
16
0
1
Order By: Relevance
“… 13 We included 82 publications in this map. 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , …”
Section: Resultsunclassified
See 3 more Smart Citations
“… 13 We included 82 publications in this map. 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , …”
Section: Resultsunclassified
“…The number of studies included for acupuncture in the reviews ranged from 1 to 73 studies. Thirty-seven reviews included fewer than 10 studies, 8 , 9 , 15 , 17 , 18 , 19 , 22 , 23 , 28 , 29 , 30 , 32 , 36 , 41 , 42 , 43 , 45 , 47 , 50 , 52 , 54 , 56 , 61 , 63 , 66 , 68 , 69 , 73 , 79 , 80 , 81 , 82 , 83 , 85 , 90 , 91 , 92 34 reviews included 10 to 25 studies, 14 , 20 , 21 , 25 , 26 , 27 , 29 , 30 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 44 , 48 , 51 , 53 , 55 , 58 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods were not the only ones that physicians also made determinations based on their clinical experience. With the deepening of clinical research, the efficacy of acupuncture on neuropathic pain has been confirmed by several systemic reviews and meta-analyses, which were listed in Table 2 ( Heo et al, 2013 ; Dimitrova et al, 2017 ; Hu et al, 2019 ; Liu et al, 2019 ; Pei et al, 2019 ; Yun et al, 2020 ; Cui et al, 2021 ; Yu et al, 2021 ). A study described the effectiveness and safety of acupuncture for the treatment of chemotherapy-induced peripheral neuropathy.…”
Section: Application Of Acupuncture For Neuropathic Painmentioning
confidence: 93%